Edukasi Gizi Seimbang pada Siswa SDN 3 Picungremuk - Annida Nihayati; Rahma Aulianisa; Listia Rahmadiana; Ismi Desmia; Riva Ahmad F; Indri Ayu Widianti (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
The low understanding of nutritious food choices among elementary school children remains a problem because it impacts their health, learning abilities, and future eating habits. A similar situation was found at SDN 3 Picungremuk, where students often choose flavored foods without considering their nutritional content. This community service activity aims to improve students' nutritional knowledge through education on the concept of